A NEW APPROACH TO TENSILE TESTING OF GFRP BARS - Mehmet Canbaz; Meltem Eryılmaz Yıldırım; Kerem Aybar (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi, 2023)
Tensile testing is a critical procedure for evaluating the mechanical properties of Glass Fiber Reinforced Polymer (GFRP) bars, which emerged as an alternative to traditional steel reinforcement in reinforced concrete structures. While significant research has led to the development of testing standards for GFRP bars, their implementation often necessitates additional specimens and specialized equipment compared to their steel counterparts. This study proposes a new method for conducting GFRP tensile tests using standard equipment designed for conventional structural steel rebar testing. By employing existing devices, our approach offers a practical and cost-effective solution for assessing the tensile properties of GFRP reinforcement. This simplified testing method aims to enhance efficiency, facilitate wider adoption of GFRP bars in reinforced concrete structures, and contribute to the advancement of sustainable construction practices.